Aspectos socioculturais do desenvolvimento produtivo urbano em angola - Cristina Udelsmann Rodrigues (Cadernos de Estudos Africanos)
The heave of productive activities in Angola, in a post-war context, is a fundamental condition to the increase of employment, to seize the informal, to the creation of formal structures that favour families’ income stability, increase social protection, and allow minimizing risks. However, the national scenery, besides being disappointing, is very heterogeneous, proving itself to be conditioned by a series of structural and economic factors. Also, and significantly, a set of sociocultural and historical factors condition the industrial scenery. In this text, some of the la!er factors are presented and analysed, a!empting, at the same time, to introduce elements of characterization of the industrial situation of some Angolan cities, and to indicate the existing weaknesses and potentials of this sector.